Treatment efficiency rate of solar powered water treatment device (SWAD) - Zawawi M.H.; Yusairah W.N.; Abidin S.Z.; Ismail I.N.; Zahari N.M. (American Institute of Physics Inc., 2023)
The solar powered water treatment device (SWAD) is an effective and affordable water treatment device using low-cost treatment materials to treat stagnant water bodies such as lakes and ponds. SWAD was designed to operate independently without being attached or relying on other machinery. Its floating features enabled SWAD to be station independently according to suitable water sections that need to be treated. This device used absorption and adsorption capacity of the activated carbon to remove pollutants as treatment element. Turbidity, colour, total suspended solid (TSS) and chemical oxygen demand (COD) were used as removal parameters in this study. Based on 48 hours of treatment the turbidity result shows about 95% removal efficiency. TSS result showed about 96% of TSS removal. The color result showed decreasing in number from 646 pt-co to 15pt-co after 48 hours of treatment. Lastly, Chemical oxygen demand (low range) shows from 173 mg/l to 7.5 mg/l for reading and the removal percentage for COD was 96%. The SWAD was successful designed. 2018 Author(s).